Does Economic Integration Process Matter for Income Inequality in Central and Eastern European Countries? - Piotrowska, Maria (Ekonomika, 2008)
Economic integration can be defined as the expansion of markets from the national to the regional or to the world level. Therefore, two channels of market integration can be determined: regional integration, for instance, within the EU, and globalization. The purpose of this paper is to investigate the impact of the economic integration process on differences in income among and within Central and Eastern European countries (CEECs). The hypotheses on 1) the economic integration relevance and 2) the mechanisms through economic integration affecting income inequality are tested with data on 10 CEECs (Bulgaria, Czech Republic, Estonia, Latvia, Lithuania, Hungary, Poland, Slovakia, Slovenia, Romania) for the 2000-2006 period. An unbalanced panel induces to estimate Random-effects regressions and fixed-effects regressions. The results show that globalization contributed significantly to income inequality among CEECs as well as to the upward trend in income inequality within the societies of these countries, while regional integration with and within the EU did not explain considerably the changes in income distribution over the study period.